2019
DOI: 10.1049/iet-nbt.2018.5179
|View full text |Cite
|
Sign up to set email alerts
|

Simple, green approach for the synthesis of solid support‐embedded PdNPs for ligand exchange

Abstract: Green approaches have the potential to significantly reduce the costs and environmental impact of chemical syntheses. Here, the authors used green tea (GT) leaf extract to synthesise and anchor palladium nanoparticles (PdNPs) to silica. The synthesised PdNPs in GT extract were characterised by ultraviolet-visible spectroscopy, Fourier-transform infrared spectroscopy, X-ray diffraction, and transmission electron microscopy. PdNPs primarily formed as capped NPs dispersed in GT extract before reduction completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…First, 1‐Thioformyl‐8‐d‐glucopyranoside‐bis‐bis‐2,3‐dihydroisopyridineo pyrrol (Figure 2) was identified as a potent active ingredient in plant extracts 20–22 . Second, we have observed that leaf extracts have the remarkable ability to produce capsulated silver nanoparticles and isotropic gold nanoparticles 18,19 . This finding has opened up exciting possibilities for the development of novel nanomaterials with a wide range of applications.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…First, 1‐Thioformyl‐8‐d‐glucopyranoside‐bis‐bis‐2,3‐dihydroisopyridineo pyrrol (Figure 2) was identified as a potent active ingredient in plant extracts 20–22 . Second, we have observed that leaf extracts have the remarkable ability to produce capsulated silver nanoparticles and isotropic gold nanoparticles 18,19 . This finding has opened up exciting possibilities for the development of novel nanomaterials with a wide range of applications.…”
Section: Introductionmentioning
confidence: 91%
“…is a widely used traditional medicinal plant in Saudi Arabia, belonging to the Zygophyllaceae family and known by various names such as African rhubarb, esf, wild rhubarb, Syrian rhubarb, harmel, or aspand. 18,19 The plant's crucial bioactive components consist primarily of alkaloids. Our investigation into the foliage of this plant is motivated by a multitude of compelling factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no straightforward approach for anchoring nano-Ag 0 to silica, despite plenty of green research into nano-Ag 0 [1]. Phytochemicals have previously been used to bind palladium nanoparticles to silica [11] and, depending on the time gap between metal ion functional group biocapping and reduction, phytochemicals can be employed as green precursors. Nano-Ag 0 -doped silica has potential applications in, for example, anti-microbial products and aqueous color extraction, and dispersing nanoparticles through solid material pores would have the advantages of increasing performance in a range of applications and providing resistance to heat and UV radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Catechins have also been shown to have several physiological effects on humans, including protection against several diseases. The majority of published studies on GT extract have focused on the production of colloidal solutions for silver and gold nanoparticles [11].…”
Section: Introductionmentioning
confidence: 99%